Clinical management and outcomes for febrile infants 29–60 days evaluated in community emergency departments. Issue 3 (17th June 2022) - Van Winkle, Patrick J.; Lee, Samantha N.; Chen, Qiaoling; Baecker, Aileen S.; Ballard, Dustin W.; Vinson, David R.; Greenhow, Tara L.; Nguyen, Tran H. P.; Young, Beverly R.; Alabaster, Amy L.; Huang, Jie; Park, Stacy; et al.
Abstract: Objective: Describe emergency department (ED) management and patient outcomes for febrile infants 29–60 days of age who received a lumbar puncture (LP), with focus on timing of antibiotics and type of physician performing LP. Methods: Retrospective observational study of 35 California EDs from January 1, 2010 through December 31, 2019. Primary analysis was among patients with successful LP and primary outcome was hospital length of stay (LOS). Logistic regression analysis included variables associated with LOS of at least 2 days. Secondary outcomes were bacterial meningitis, hospital admission, length of antibiotics, and readmission. Results: Among 2569 febrile infants (median age 39 days), 667 underwent successful LP and 633 received intravenous antibiotics. Most infants ( n  = 559, 88.3%) had their LP before intravenous antibiotic administration. Pediatricians performed 54% of LPs and emergency physicians 34%. Sixteen infants (0.6% of 2569) were diagnosed with bacterial meningitis, and none died. Five hundred and fifty‐eight (88%) infants receiving an LP were hospitalized. Among patients receiving an LP and antibiotics ( n  = 633), 6.5% were readmitted within 30 days. Patients receiving antibiotics before LP had a longer length of antibiotics (+ 7.9 hours, 95% confidence interval [CI] 3.8–13.4). Primary analysis found no association between timing of antibiotics and LOS (odds ratio [OR] 0.67, 95% CI 0.34–1.30), but shorter LOS when emergency physicians performed the LP (OR 0.66, 95% CI 0.45–0.97). Conclusions: Febrile infants in the ED had no deaths and few cases of bacterial meningitis. In community EDs, where a pediatrician is often not available, successful LP by emergency physician was associated with reduced inpatient LOS.